THE CORRELATION BETWEEN THE VOCABULARY KNOWLEDGE AND THE SPEAKING SKILLS OF THE SECOND YEAR STUDENTS OF SMA ISLAM AS-SHOFA PEKANBARU - Yuwandi, Aditya Deonanda; Azhar, Fadly; ', Marzuki (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The Objective of this research is to find out the significant correlation between the vocabulary knowledge and the speaking skills of the second year students of SMA Islam As-Shofa Pekanbaru. The sample of this research was class XI IIS 2, which consisted of 23 students. The data were collected using two kinds of test; namely, a vocabulary test and a speaking test. The results of this research showed that the second year students of SMA Islam As-Shofa Pekanbaru got excellent level with the average score of 84.75 in vocabulary and 77.39 in speaking test which are considered as in Good Level. The results of this research proved that there was a positive correlation between the vocabulary knowledge and the speaking skills of SMA Islam As-Shofa Pekanbaru. The Rxy distribution of the coefficient correlation was 0,83. It means that there was a very high correlation between these two variables. It means that the Ho (null hypotheses) was rejected and the H1 (alternative hypotheses) was accepted. Therefore, it can be concluded that the vocabulary knowledge has a correlation with the speaking skills.Keywords : Correlation, Vocabulary Knowledge, Speaking Skills